PENGARUH PEMBERIAN Mg DAN Fe TERHADAP KANDUNGAN VITEKSIKARPIN DAUN LEGUNDI (Vitex trifolia) PADA TIGA ORDO TANAH - , ANNA KUSUMAWATI; , Dr. Ir. Eko Hanudin, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research was conducted to observed the effect of Mg and Fe application to the vitexicarpin content in the leaves of Legundi (Vitex trifolia), to determine the most suitable type order of soil (Andisol, Alfisol, and Inceptisol) and to find the best harvest time which obtained the highest content of Vitexicarpin. This research was conducted in the green house of Soil Science Department of Agricultural Faculty, Gadjah Mada University. The experiment was arranged in a Completely Randomized Design (CRD) with three treatment factors. The first factor is the order of soil: Andisol (An), Alfisol (Al), and the Inceptisol (In). The second factor is the dosage of MgSO4 fertilizer : 0 kg/ha (Mg0)